Long Intergenic Non-Coding RNAs: Novel Drivers of Human Lymphocyte Differentiation - Panzeri, Ilaria; Rossetti, Grazisa; Abrignani, Sergio; Pagani, Massimiliano (Frontiers in Immunology, 2015)
Upon recognition of a foreign antigen, CD4+ naïve T lymphocytes proliferate and differentiate into subsets with distinct functions. This process is fundamental for the proper immune system function, as CD4+ T cells orchestrate both the innate and adaptive immune response. Traditionally, this differentiation event has been regarded as the acquisition of an irreversible cell fate so that memory and effector CD4+ T subsets were considered terminally differentiated cells or lineages. Consequently, these lineages are conventionally defined thanks to their prototypical set of cytokines and transcription factors. However, recent findings suggest that CD4+ T lymphocytes possess a remarkable phenotypic plasticity, as they can often redirect their functional program depending on the milieu they encounter. Therefore new questions are now compelling such as which are the molecular determinants underlying plasticity and stability and how the balance between these two opposite forces drives the cell fate. As already mentioned, in some cases the mere expression of cytokines and master regulators could not fully explain lymphocytes plasticity. We should consider other layers of regulation, including epigenetic factors such as the modulation of chromatin state or the transcription of noncoding RNAs, whose high cell-specificity give a hint on their involvement in cell fate determination. In this review, we will focus on the recent advances in understanding CD4+ T lymphocytes subsets specification from an epigenetic point of view. In particular, we will emphasize the emerging importance of noncoding RNAs as key players in these differentiation events. We will also present here new data from our laboratory highlighting the contribution of long noncoding RNAs in driving human CD4+ T lymphocytes differentiation.